2013
DOI: 10.1186/2193-1801-2-252
|View full text |Cite
|
Sign up to set email alerts
|

Haliscosamine: a new antifungal sphingosine derivative from the Moroccan marine sponge Haliclona viscosa

Abstract: In the aim of searching for new antifungal products from marine origin, we have isolated a sphingosine derivative, (9Z)-2-amino-docos-9-ene-1,3,13,14-tetraol (Haliscosamine) from the Moroccan sea sponge Haliclona viscosa using bio-guided (antifungal) HPLC methods. The molecular structure of this compound was elucidated by spectrometric techniques IR, UV, MS and NMR. The isolated metabolite showed a significant antifungal activity against Cryptococcus and Candida species and a weak general toxicity in the brine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Sphingolipids are already known for their antiseptic and antifungal activity (Bibel et al ., ), and sphingosine and its derivatives are natural antimicrobial agents, protecting the human skin from bacterial colonization (Bibel et al ., , ) as well as being anti‐inflammatory agents (Radhika et al ., ). The Moroccan invertebrates and especially sponges are poorly studied (Rifai et al ., , ; El‐Amraoui et al ., ; El‐Wahidi et al ., ), but are a promising source of new compounds with diverse biological activities (El‐Amraoui et al ., ; El‐Wahidi et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingolipids are already known for their antiseptic and antifungal activity (Bibel et al ., ), and sphingosine and its derivatives are natural antimicrobial agents, protecting the human skin from bacterial colonization (Bibel et al ., , ) as well as being anti‐inflammatory agents (Radhika et al ., ). The Moroccan invertebrates and especially sponges are poorly studied (Rifai et al ., , ; El‐Amraoui et al ., ; El‐Wahidi et al ., ), but are a promising source of new compounds with diverse biological activities (El‐Amraoui et al ., ; El‐Wahidi et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Haliscosamine is an sphingosine derivative, (9Z)‐2‐amino‐docos‐9‐ene‐1,3,13,14‐tetraol (Haliscosamine) isolated from the Moroccan sea sponge H. viscosa as described in (El‐Amraoui et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…In other studies, the antifungal compound from Haliclona sp. was discovered (Clark et al, 2001;Wattanadilok et al, 2007;El-Amraoui et al, 2013). Antifungal compounds were isolated from Haliclona include a sphingosine derivatives, named haliscosamine from from the Moroccan marine sponge Haliclona viscose (El-Amraoui et al, 2013), nortetillapyrone from Haliclona cymaeformis, collected from the Gulf of Thailand (Wattanadilok et al,2007), and alkyl amino alcohols, halaminols A-C from sponge Haliclona sp., collected on the Great Barrier Reef (Clark et al, 2001).…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…El-Amraoui et al reported the structure elucidation of the antifungal haliscosamine 70 (Figure 7.29), a new sphisgosine derivative, isolated from the Moroccan marine sponge Haliclona viscosa [92]. The 1 H NMR spectrum revealed the presence of 45 protons in the range of 0.9 to 5.4 ppm, while the 13 C APT spectrum (the Attached Proton Test experiment is a common way to assign C-H multiplicities in 13 C NMR; the phase of CH and CH 3 peaks is 180° different from C and CH 2 peaks) combined with the HSQC spectrum identified 22 carbons (1 methyl, 15 methylene, and 6 methines) bounded to 39 protons.…”
Section: Combined Nmr Techniques and Different Families Of Compoundsmentioning
confidence: 99%